A Study of Land Tenure in the Old Babylonian Period with Special Reference to the Diyala Region, based on published and unpublished texts - Suleiman, Amer
Ph.D.; Supervisor: H. W. F. Saggs; Part One: I. Introduction. 1. General Remarks; 2. The Main Cities of the Diyala Region in the Old Babylonian Period; 3. The System of Land Tenure in South Mesopotamia prior to the Old Babylonian Period; II. The System of Land Tenure in the Old Babylonian Period: Crown-Lands; III. Privately-owned Lands; IV. Conclusions. — Part Two: I. Transliteration and Translation of Unpublished Texts from Tell al-Ḍiba‛i and Tell Ḥarmal with Philological Notes: II. Index of Personal Names (pp. 404-416a); III. Cuneiform Copies of D2 112 (Ḍiba‛i, 1); 269 (21); 278 (29); 318 (30); 438/1 (42); 188 (61); 24 (85); IM 55109/1 (Ḥarmal 35); 55460 (36); 63152 (37); 63172 (38); 63248/1 (39); 63248/2 (39); 63249 (40); 63157 (41); 63150 (43); 63181 (44); 54999/1 (45); 54991/2 (45); 54695/1 (46); 54695/2 (46); 63209/1 (47); 63209/2 (47); 63314/1 (48); 63174 (49); 52433 (50); 54685 (51): 63160 (52); 63183 (53); 63130 (55); 55433 (82); 63192 (83); 63236/1 (84); 63243 (86).